2021
DOI: 10.1002/pc.25928
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne epoxy sizing agent with hyperbranched structure to improve the interface performance of carbon fiber

Abstract: The epoxy resin was modified by hyperbranched structure of hydroxyl terminated to obtain waterborne epoxy resin for using as the carbon fiber (CF) sizing agent. By mixing method of waterborne epoxy resin and water, the waterborne epoxy sizing agent can be fabricated directly. In the sizing process, free of volatile organic solvents ensure the safety of operators and environment. Moreover, the introduction of tertiary amine group in hyperbranched structure will promote the reaction between epoxy and hydroxyl gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…FT‐IR results show that characteristic spectral peaks of the four coatings are similarity, including OH (2966 cm −1 ), CCH 2 C (2921 cm −1 , 2869 cm −1 ), CO (1610 cm −1 ), benzene ring (1510 cm −1 , 1458 cm −1 ), aromatic ether (1247 cm −1 , 1182 cm −1 ), CO of alkyl alcohol (1035 cm −1 ), CO of phenol (1182 cm −1 ), and CH of aromatic (827 cm −1 ), which is probably due to the characteristic spectral peaks of groups in fillers grafted on epoxy resin are covered by epoxy resin, and the contents of fillers are too low to show up the characteristic spectral peaks (Figure S5). 27,28 …”
Section: Resultsmentioning
confidence: 99%
“…FT‐IR results show that characteristic spectral peaks of the four coatings are similarity, including OH (2966 cm −1 ), CCH 2 C (2921 cm −1 , 2869 cm −1 ), CO (1610 cm −1 ), benzene ring (1510 cm −1 , 1458 cm −1 ), aromatic ether (1247 cm −1 , 1182 cm −1 ), CO of alkyl alcohol (1035 cm −1 ), CO of phenol (1182 cm −1 ), and CH of aromatic (827 cm −1 ), which is probably due to the characteristic spectral peaks of groups in fillers grafted on epoxy resin are covered by epoxy resin, and the contents of fillers are too low to show up the characteristic spectral peaks (Figure S5). 27,28 …”
Section: Resultsmentioning
confidence: 99%
“…The methods used to enhance the bonding performance of the interface between carbon fiber and resin usually include surface modification, surface sizing treatment, surface insertion of nanomaterial, and multiscale reinforcing materials 7,13,15–20 . Among the above methods, the sizing treatment is more widely used due to many advantages such as a simple treatment process, flexible method, and easy industrial production 9,21,22 . The sizing agent can form a protective layer on the surface of the carbon fiber, converge and reduce burrs, and provide reactive groups at the same time to improve the interface bonding performance between CF and the matrix 23 …”
Section: Introductionmentioning
confidence: 99%
“…7,13,[15][16][17][18][19][20] Among the above methods, the sizing treatment is more widely used due to many advantages such as a simple treatment process, flexible method, and easy industrial production. 9,21,22 The sizing agent can form a protective layer on the surface of the carbon fiber, converge and reduce burrs, and provide reactive groups at the same time to improve the interface bonding performance between CF and the matrix. 23 Polyurethane films are widely used in coatings, adhesives, biomedicine, the textile industry, and the paper industry due to their excellent elasticity and abrasion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that stacking sequence had a great influence on CAI strength and the 45 specimen had the maximum contact reaction, the minimum maximum-center-displacement and the maximum CAI strength. Liu et al [7] studied the influence of impact energy levels (15,30,45, and 60 J) and the stacking sequences ([0 /90 ] 8S and [0 /45 /90 /À45 ] 4S ) on the CAI of composites. They discovered that the peak impact force of the two different stacking sequences increased from 7.8/8.3 kN to 11.4/13.7 kN, and the CAI strength decreased from 370.5/419.3 MPa to 212.8/232.5 MPa, respectively.…”
mentioning
confidence: 99%
“…[12,13] In addition, as the medium of load transfer between fiber and resin in composites, the properties of interfacial directly affects the load transferring efficiency between fiber and resin, and then affects the final mechanical properties of composites, playing an important role in the properties of composites. [14,15] Therefore, improving the interfacial properties of composites has been a hot research issue. Various methods have been used to modify the surface of carbon fibers to improve the interfacial properties of composites, such as oxidation, [16,17] plasma treatment, [18,19] chemical grafting, [20,21] high-energy irradiation, [22][23][24] nanoparticles.…”
mentioning
confidence: 99%